Integrating gender mainstreaming in disaster risk reduction through providing geospatial information to create community resilience in Muntuk Village, Bantul Regency - Alfarizi, M. Zaky; Salsabila, Sonia Nada; Fitriyah, Istiadatul; Fajarwati, Alia (EDP Sciences, 2023)
Muntuk Village, Bantul Regency has a high multi-risk disaster potential, in the form of earthquakes and landslides. This is due to the location of Muntuk Village which is in the Bukit Batur Agung formation and is directly connected to the Opak Fault. The implications of these threats result in high disaster vulnerability. The focus of this research is to examine aspects of social vulnerability with the main subject being women, especially since the number of victims of the 2006 Bantul earthquake was dominated by women. This research seeks to integrate the development of Prima Village to increase the resilience of women's communities. The method used is a concurrent mixed method using questionnaires, interviews, and observations, as well as mapping data processing. The results of the analysis produced several outputs, including Sex Ratio Map, Economic Resilience Index Map, Prima Village Feasibility Standard Map, Landslide Prone Area Map, Logistics Warehouse Coverage Effectiveness Map, Logistics Warehouse Development Plan Map, and policy recommendations. It is hoped that this output can be used as input in designing regional disaster planning policies, both pre-disaster, during a disaster, and post-disaster, especially for women to improve community empowerment programs to achieve the goals of Prima Village. © 2023 EDP Sciences. All rights reserved.